2020
DOI: 10.1111/jpm.12713
|View full text |Cite
|
Sign up to set email alerts
|

The influence of minority stress on indicators of suicidality among lesbian, gay, bisexual and transgender adults in Thailand

Abstract: Accessible summary What is known on the subject? Established research from the United States and other Western countries has found that lesbian, gay, bisexual and transgender (LGBT) populations are at an elevated risk for suicide. Suicidality among LGBT individuals is understudied in Thailand and other Asian countries, warranting additional research to better understand risk factors and to create effective treatment and suicide prevention interventions. What the paper adds to existing knowledge? The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…Suicidality was higher among transgender respondents than cisgender respondents, and was higher among transgender boys than transgender girls. Depression and suicidality among Thai transgender youths are associated with victimization and internalized homophobia [ 8 , 9 ], as well as family rejection and social isolation [ 31 ]. The Thai media also contains hetero-sexist narratives, harmful and discriminatory rhetoric, and negative portrayals of LGBTIQ people [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suicidality was higher among transgender respondents than cisgender respondents, and was higher among transgender boys than transgender girls. Depression and suicidality among Thai transgender youths are associated with victimization and internalized homophobia [ 8 , 9 ], as well as family rejection and social isolation [ 31 ]. The Thai media also contains hetero-sexist narratives, harmful and discriminatory rhetoric, and negative portrayals of LGBTIQ people [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found minority stress (i.e., stress faced by members of stigmatized minority groups caused by factors such as lack of social support, low socioeconomic status, interpersonal prejudice, and discrimination) in the Thai homosexual and bisexual men population [ 33 ]. It is possible that minority stress and internalization of rejection, discrimination and violence [ 9 , 34 ] could have accounted for disparities in depression and suicidality between Thai cisgender and transgender adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the search, we obtained a total of 381 records, of which 16 articles were selected: 1 systematic review and meta-analysis [28], 5 systematic reviews [29][30][31][32][33], 1 cross-sectional descriptive study [34], 4 qualitative studies [35][36][37][38], and 5 quasi-experimental pre-testpost-test studies [39][40][41][42][43]. Regarding the variables of the reviews, 6 articles addressed the specific health needs of LGBT people [28,29,[31][32][33][34], 3 focused on LGBT people's experiences and perceptions [35][36][37], and 10 presented nursing interventions in the LGBT community [30][31][32][33][38][39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of national contexts, 5 studies were conducted in the USA [38,39,[41][42][43], 2 in Canada [36,40], 1 in Ireland [37], 1 in Turkey [35], and 1 in Thailand [34]. According to the classification by the World Bank [44], 8 articles were from high-income economies (the USA, Canada, and Ireland) and 2 were from upper-middle-income economies (Turkey and Thailand).…”
Section: Resultsmentioning
confidence: 99%